Phenotypic characterization and candidate gene analysis of a short kernel and brassinosteroid insensitive mutant from hexaploid oat (Avena sativa) - Tsardakas Renhuldt, Nikos; Bentzer, Johan; Ahrén, Dag; Marmon, Sofia; Sirijovski, Nick (Frontiers in Plant Science, 2024)
In the present study, we have identified and characterised an oat (Avena sativa) mutant from an ethyl methanesulfonate (EMS) population with short kernels, compact spikelets, and altered plant architecture when compared to the wild type (WT) cv. Belinda. By crossing the mutant with the WT cv., we found that the segregation of WT and mutant phenotypes in the F 2 population was indicative of a recessive mutation of a single locus. Following bulked segregant analysis (mappingby-sequencing), the causal mutation was found to be one of 123 single nucleotide polymorphisms (SNPs) spanning the entire chromosome 3A. Using the reference genome annotation and filtering SNPs for those occurring in genes within chromosome 3A and having a moderate-to-high predicted impact on function, we narrowed in on six candidate genes. In depth analysis of these candidate genes and complementary brassinosteroid sensitivity assays suggests that a Pro303Leu substitution in AVESA.00010b.r2.3AG0419820.1 could be the causal mutation of the short kernel mutant phenotype. The AVESA.00010b.r2.3AG0419820.1 candidate is functionally annotated as a GSK3/SHAGGY-like kinase with homologs in Arabidopsis, wheat, barley, rice, and maize, with several of these proteins having known mutants giving rise to brassinosteroid insensitivity and shorter seeds. The substitution in AVESA.00010b.r2.3AG0419820.1 affects a residue with a known gainof-function substitution in Arabidopsis BRASSINOSTEROID-INSENSITIVE 2. We also identify 298 oat proteins belonging to orthogroups of previously published seed shape genes, with AVESA.00010b.r2.3AG0419820.1 being the only of these having a SNP in the mutant.